Blood cleaner on-chip design for artificial human kidney manipulation - Preecha Yupapin; Nathaporn Suwanpayak; None Jalil; None Teeka; None Ali; None Ma; None Aziz (My University, 2011)
Abstract: A novel design of a blood cleaner on-chip using an optical waveguide known as a PANDA ring resonator is proposed. By controlling some suitable parameters, the optical vortices (gradient optical fields/wells) can be generated and used to form the trapping tools in the same way as optical tweezers. In operation, the trapping force is formed by the combination between the gradient field and scattering photons by using the intense optical vortices generated within the PANDA ring resonator. This can be used for blood waste trapping and moves dynamically within the blood cleaner on-chip system (artificial kidney), and is performed within the wavelength routers. Finally, the blood quality test is exploited by the external probe before sending to the destination. The advantage of the proposed kidney on-chip system is that the unwanted substances can be trapped and filtered from the artificial kidney, which can be available for blood cleaning applications. Keywords: optical trapping, blood dialysis, blood cleaner, human kidney manipulation
Keywords: Lab-on-a-Chip; Waveguide; Orbital Angular Momentum in Optics